Persistent hydatidiform mole following incomplete evacuation mimicking post-molar gestational trophoblastic neoplasia successfully managed with repeat suction curettage: a case report - Mala Hayati; Cut Meurah Yeni; Rizka Aditya (Journal of International Surgery and Clinical Medicine, 2026)
Introduction: Hydatidiform mole is the most common form of gestational trophoblastic disease and may progress to post-molar gestational trophoblastic neoplasia (GTN). Persistent vaginal bleeding and elevated β-hCG levels following molar evacuation may indicate persistent trophoblastic disease and create diagnostic challenges, particularly when histopathological evaluation is unavailable. Case Report: A 27-year-old woman was referred with persistent vaginal bleeding five months after suction curettage for a hydatidiform mole. Histopathological examination was not performed during the initial evacuation because the anatomical pathology service was unavailable. Physical examination revealed uterine enlargement and active vaginal bleeding. Serum β-hCG was markedly elevated at 223,759 mIU/mL, and ultrasonography demonstrated an enlarged uterus with a heterogeneous honeycomb appearance suggestive of hydatidiform mole. The patient underwent repeat suction curettage, and histopathological examination demonstrated persistent hydatidiform mole without evidence of malignancy. Serial β-hCG monitoring showed progressive decline to <2 mIU/mL without chemotherapy. Discussion: Persistent trophoblastic disease following incomplete evacuation may clinically resemble post-molar GTN because of persistent bleeding, uterine enlargement, and markedly elevated β-hCG levels. Histopathological evaluation and serial β-hCG surveillance were essential in distinguishing persistent hydatidiform mole from malignant trophoblastic disease. Repeat suction curettage facilitated definitive diagnosis and complete remission in this patient. Conclusion: Persistent trophoblastic disease secondary to incomplete evacuation of a hydatidiform mole may mimic post-molar GTN. Repeat suction curettage may represent an effective management option in carefully selected low-risk patients with disease confined to the uterus.